INOVASI PENGELOLAAN TAMAN BACAAN MASYARAKAT SEBAGAI STRATEGI MENINGKATKAN LITERASI ANAK USIA SEKOLAH - Anni Malihatul Hawa; Sawaluddin Siregar; Hesti Yunitiara Rizqi; Suyitno (Marsialapari: Jurnal Pengabdian Kepada Masyarakat, 2025)
The low reading interest of school-age children in West Pasaman Regency presents a serious challenge to the development of education and a culture of literacy. This community service program aims to develop innovative management of Community Reading Parks (TBM) as a strategy to improve children's literacy. The background of the activity is based on the fact that most TBMs in this region are not optimally managed, lack innovation, and lack engaging activities for children. The implementation method uses a participatory approach involving TBM managers, teachers, parents, and literacy volunteers. Activities include TBM management training, the provision of creative reading corners, the development of educational game-based literacy programs, and regular mentoring for children. Innovations implemented include storytelling corners, weekly reading clubs, and the integration of simple digital media to attract the interest of the younger generation. The results of the activity show an increase in children's enthusiasm in utilizing TBMs, marked by an increase in the number of daily visits and active involvement in literacy activities. Furthermore, the capacity of TBM managers to design sustainable programs has increased. This program demonstrates that innovative TBM management can be an effective strategy in fostering a culture of literacy among school-age children in West Pasaman.